2017
DOI: 10.1161/jaha.116.004756
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of CD137 Signaling Promotes Angiogenesis in Atherosclerosis via Modulating Endothelial Smad1/5‐NFATc1 Pathway

Abstract: BackgroundExcessive angiogenesis is a key feature of vulnerable atherosclerotic plaques, and is considered an independent predictor of cardiovascular risk. CD137 signaling has previously been shown to be involved in atherosclerosis. However, the possible role of CD137 signaling in regulating angiogenesis has not been reported.Methods and ResultsApolipoprotein E‐deficient (ApoE−/−) mice were used as the in vivo model of atherosclerosis. Masson and immunohistochemical analysis of atherosclerotic plaques and Matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…In our previous studies, CD137‐CD137L signalling has been shown to be involved in AS . We have also demonstrated that increased CD137 level may contribute to the instability of atherosclerotic lesion.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…In our previous studies, CD137‐CD137L signalling has been shown to be involved in AS . We have also demonstrated that increased CD137 level may contribute to the instability of atherosclerotic lesion.…”
Section: Introductionmentioning
confidence: 62%
“…Emerging evidence has revealed that CD137‐CD137L signalling plays an important role in the plaque inflammation during AS development . However, it remains unclear whether EC‐derived exosomes participate in the Th17 cell differentiation, and if so, whether CD137‐CD137L signalling can regulate the immunoregulatory properties in AS development.…”
Section: Discussionmentioning
confidence: 99%
“…The aortic ring assay is a well-accepted method for evaluating angiogenesis ( Gimenes et al, 2017 ; Weng et al, 2017 ): thoracic aortas were isolated, cut into rings, and used in the aortic ring assay as previously described. Microvessel sprouts began to merge at day 3 in aortic rings from mice treated with either NSD or HSD for consecutive 12 week.…”
Section: Resultsmentioning
confidence: 99%
“…Angiogenesis is an important factor that influences the development of atherosclerotic plaques and is closely associated with local neovascularization and plaque stability ( 1 ). It has been demonstrated that excessive angiogenesis is associated with intraplaque hemorrhage, suggesting that neovascularization may contribute to lesion progression and rupture ( 2 ). Rupture-prone vulnerable plaques exhibit high lipid infiltration, increased numbers of inflammatory cells, a thin fibrous cap, and extensive endometrial and adventitial neovascularization ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%